Variación espacial y temporal en la composición de la dieta de peces invertívoros en un río neotropical, Venezuela - Ortaz, Mario (Universidad de Costa Rica, 2011)
Invertivores fishes are an important component of neotropical streams and they represent a link between aquatic invertebrates and piscivorous species. This study evaluated the breadth diet and interspecific food overlap of nine invertivores fish species during three consecutive hydrological phases: falling (December/07, January/08, February/08 and March/08), low (April/08) and rising waters (June/08), in two sections of a Venezuelan neotropical stream, which were located at different elevation, high watershed (HW) and low watershed (LW). The fishes were collected with a beach seine (5mm mesh) between 8:00 and 11:00 hours. The diet of each species was evaluated using an index of relative importance (IRI), which includes as variables the number, weight and occurrence frequency of food items consumed. The Levin' index (B i) and Morisita (IM) were used to estimate the breadth diet and interspecific food overlap, respectively. All estimations were made using the numeric proportion of preys. Nine fish species were captured, eight Characiformes, of which three were captured in HW (Knodus deuteronoides, Creagrutus bolivari and C. melasma) and five in LW (Thoracocharax stellatus, Moenkhausia lepidura, Cheirodon pulcher, Ctenobrycon spilurus and Aphyocharax alburnus), and one Cyprinodontiformes (Poecilia reticulata), which was also found in HW. In HW aquatic insects were the main resource consumed by fishes while plant material and terrestrial arthropods were secondary resources. In LW the fishes ingested all of these items in addition to zooplankton (Copepoda, Cladocera and larval stages of Decapoda). However, there was a temporal replacement with a predominance of zooplankton in falling and low water. In general, the breadth diet decreased during the falling water in both sections and increased in rising water. However, the average breadth diet was higher in HW. The interspecific food overlap was high in HW while low values were more frequent in LW and its temporal variation was opposed in both sections during almost all the sampling period.